HOW THE INSTITUTIONAL SYSTEM CHARGED WITH REGIONAL DEVELOPMENT POLICY ACTUALLY IMPACT THE USE OF COHESION FUNDS AS REFLECTED BY A COMPARATIVE ANALYSIS OF POLAND AND HUNGARY - Gabriella Gyorine Szabo (European Scientific Journal, ESJ, 2014)
After ten years of membership visible differences in the way the two countries use development funds intended for convergence are beginning to evolve although both joined the European Union at the same time. Despite the similarities in the problems needing to be remedied through their regional development policies, identical timeframes and the proportionately equal development funds, there is an order of magnitude in the differences in the quantitative use of the cohesion funds in the final third of the seven-year programme. Hungary is nearly 20 percent behind Poland in absorption of the Cohesion Fund and the European Social Fund, and according to European Commission statistics published in November 2013 Poland is also ahead in accessing the Regional Development Fund. This paper is intended to explore institutional differences in the in the regional policies of the two countries, how they evolved, and how they were amended over time. My investigation covers the institutions and fund usage starting with accession to the European Union and ending with the programme cycle of 2007-2013, as well as progress in preparations for the Partnership Agreement and operative programmes that follow adoption of the joint (EP and EC, 2013) directives for the 2014-2020 budget period. This study does not cover political regionalism and is limited to the role of the regional institutional systems from the aspect of professional policy.